2012
DOI: 10.1016/j.forsciint.2011.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fingermarks by colloidal gold (MMD/SMD) – beyond the pH 3 limit

Abstract: This work is part of a continuing goal to improve the multimetal deposition technique (MMD), as well as the single-metal deposition (SMD), to make them more robust, more user-friendly, and less labour-intensive. Indeed, two major limitations of the MMD/SMD were identified: (1) the synthesis of colloidal gold, which is quite labour-intensive, and (2) the sharp decrease in efficiency observed when the pH of the working solution is increased above pH 3. About the synthesis protocol, it has been simplified so that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…To further simplify the technique, the first SMD I step was revisited in 2012 (Bécue, Scoundrianos, & Moret, 2012). A simpler colloidal gold synthesis protocol was chosen and a small amount of amino acid (L-aspartic acid) was added during the synthesis.…”
Section: Multimetal Depositionmentioning
confidence: 99%
“…To further simplify the technique, the first SMD I step was revisited in 2012 (Bécue, Scoundrianos, & Moret, 2012). A simpler colloidal gold synthesis protocol was chosen and a small amount of amino acid (L-aspartic acid) was added during the synthesis.…”
Section: Multimetal Depositionmentioning
confidence: 99%
“…Despite its universal ability in visualizing latent fingerprints on a wide range of porosity (Saunders 1989;Zhang et al 2007), this silver-on-gold method is rarely applied in practical caseworks (Becue et al 2012), attributable to major drawbacks which include the use of expensive reagents and scrupulously clean glassware, laborious procedures (at least 1 h of processing due to the requirement of many immersion baths) (Saunders 1989;Ramotowski 2012b), and the possibility of over-development of prints (Becue et al 2012;Ramotowski 2012b). In addition, MMD-I also suffers from limited working pH (~pH 3) (Saunders 1989;Becue et al 2012); at higher pH, significant decrease in the efficiency of the method was observed (Bécue and Cantú 2012;Becue et al 2012). Such outcome is observed due to the loss of electrostatic attraction between the positively charged constituents of fingerprints (water-insoluble proteins that are trapped within the lipids) and negatively charged citrate-capped colloidal gold nanoparticles (Schnetz and Margot 2001;Becue et al 2007;Bécue and Cantú 2012).…”
Section: Multi Metal Depositionmentioning
confidence: 99%
“…Since pH is an important factor in MMD method, this can be suggestive that the pH working range for this method being narrow. The addition of aspartic acid conjointly with sodium citrate during the synthesis of gold has significantly extended the working pH of SMD (from pH 2 to pH 6.7), hence improving the robustness of the method (Becue et al 2012). Although the increased quality of visualized fingerprints at low pH is characterized by the increased electrostatic interactions (since aspartic acid has a lower pKa value), the active role of aspartic acid in allowing the detection of fingerprints at an extended working range of pH remains baffling.…”
Section: Single Metal Depositionmentioning
confidence: 99%
“…The multimetal deposition (MMD) introduced by Saunders et al [36] in 1989 is a very sensitive method for visualizing LFPs on a range of surfaces. Since then, a great deal of effort has been devoted to reducing the labor-intensity of this procedure [37][38][39]. Recently, MMD has been performed in a reverse manner by developing a paper substrate rather than fingerprint residue [40,41].…”
Section: New Materialsmentioning
confidence: 99%